Médias Et Mondialisation : Quelle Place Pour Le Dialogue Interculturel - Haddadi, Radhia (الإحياء, 2024)
Since its inception and over the decades, media and communication, with their diversity, have an unparalleled influence which becomes part of everyday life; under this influence are built a lot of decisions and justified a lot of behaviors. And with that, and in the light of globalization, we put forward the problematic of the role and which depends firstly the logique of the media then the communication; thus the possibility of creating contact between human societies. Has the information, which is the base of each communication, become just a trade? And can we upgrade it to a mean for knowing the other with all his differences? Is the following of the development means full melting and vanishing in the corridors and mysteries of globalization; therefore communication will disappear even in its simplest form?